Chemotherapy strategies for young children newly diagnosed with desmoplastic/extensive nodular medulloblastoma up to the era of molecular profiling – a comparative outcomes analysis of prospective multi-center European and North American trials. (15th October 2021) - Finlay, Jonathan; Mynarek, Martin; Dhall, Girish; Lafay-Cousin, Lucie; Mazewski, Claire; Ashley, David; Leary, Sarah; Cohen, Bruce H; Robinson, Giles; Geyer, Russell; Tait, Diana; Stanek, Joseph; et al.
Abstract: Aims: Survival has been poor in several multi-center/national trials since the 1980s, either delaying, avoiding or minimizing brain irradiation in young children with medulloblastoma. The introduction of German regimens supplementing "standard" chemotherapy with both intravenous high-dose (HD-MTX) and intraventricular (IVENT-MTX) methotrexate, and North American regimens incorporating marrow-ablative chemotherapy with autologous hematopoietic cell rescue (HDCx+AuHCR), have reported encouraging outcomes. We performed a comparative outcomes analysis of these differing strategies for young children with desmoplastic/extensive nodular medulloblastoma. Method: Data from 12 trials reported between 2005 and 2020 for children <six-years-old with desmoplastic/extensive nodular medulloblastoma were reviewed; event-free (EFS) survival+/-standard errors were compared. Results: The German HIT-SKK'92 and HIT-SKK'00 trials incorporating HD-MTX and IVENT-MTX reported 85+/-8% and 95+/-5% 5-10-year EFS respectively; a third trial (ACNS1221) incorporating HIT-SKK therapy but without IVENT-MTX reported only 49+/-10% EFS. Three trials (Head Start I and II combined and CCG-99703) employing induction chemotherapy without HD-MTX, followed by one or three HDCx+AuHCR cycles, reported 3-5-year EFS of 67+/-16% and 79+/-11%. Two trials employing HD-MTX-containing induction chemotherapy (Head Start III and ACNS0334), followed by one or three HDCx+AuHCR cycles, reported 3-5-year EFS of 89+/-6% and 100%, respectively. Finally, four trials utilizing neither IVENT-MTX nor HDCx+AuHCR (UK-CNS-9204, CCG-9921, COG-P9934 and SJYC07) reported 2-5 year EFS of 35+/-11%, 77+/-9%, 58+/-8% and 53+/-9% respectively. Conclusion: A trend towards better EFS for young children with desmoplastic/extensive nodular medulloblastoma is observed in trials including eitherHD-MTX and IVENT-MTX or including HD-MTX-containing induction chemotherapy and HDCx+AuHCR. Trials excluding HD-MTX, IVENT-MTX and HDCx+AuHCR have poorer outcomes.